Implementasi Nilai-Nilai Pendidikan Sosial Religius Remaja Karang Taruna Desa Salam Sari, Kedu, Temanggung - Dita Indah Sari; Maryono; Salis Irvan Fuadi (Student Research Journal, 2023)
This study aims to analyze the implementation of the values ​​of socio-religious education in Karang Taruna youth in Salam Sari Village, Kedu, Temanggung. Socio-religious education is an important component in shaping the character of adolescents who are ethical, responsible and have good social skills. This study uses qualitative research methods with data collection techniques through observation, interviews, and documentation. Respondents in this study were Karang Taruna youth who were active in Salam Sari Village. Data analysis was performed using thematic analysis. The results showed that the implementation of the values ​​of socio-religious education in Karang Taruna youth of Salam Sari Village was carried out through several strategies. First, through the implementation of religious activities such as recitation, study of the scriptures, and religious-based togetherness activities. Second, by developing social skills through leadership training, teamwork, and self-development. The implementation of these socio-religious educational values ​​has had a positive impact on the youth of Karang Taruna in Salam Sari Village. Teenagers are becoming more aware of the importance of morals and ethics in everyday life. They are also able to develop social skills that are useful in interacting with the surrounding community. In addition, teenagers also feel involved in religious activities which provide a deeper understanding of religion and spirituality.